Covid-19 pandemic: a geopolitical analysis - Souza, Jose Gilberto [UNESP]; Guimaraes, Raul [UNESP] (Univ Sao Paulo, Fac Saude Publica, 2021)
From a critical re-elaboration of the Gramsci's analytical categories of war of position and war of movement, in an inter-scale perspective, the different power structures and how they position themselves in the face of the global health crisis in search of hegemony are analyzed. Such perspectives point to the covid-19 pandemic as a geopolitical issue and highlight how the strategies of supra-state bodies (WTO, WHO, ILO), States and sectoral economic groups materialize as territorial determinations developed over a fragmented civil society, particularly in the most vulnerable strata ( indigenous peoples, peasants and black communities). These territorial determinations express a set of power relations for the realization of the form of value.
Keywords: War of Position; War of Movement; Territorial Determinations; Power Relations